Senior power or senior peril : aged communities and American society in the twenty-first century - Bramlett, Brittany H., 1984- (Social logic of politics., 2015)
As the Baby Boomer generation ages, the number of senior citizens as a proportion of the overall electorate is going to reach record numbers. This fact prompted Brittany Bramlett to ask: When senior citizens make up a large proportion of the local population, are they politically more powerful, or are they perhaps more powerless? In Senior Power or Senior Peril, Bramlett examines the assertions that the increasing number of older adult-concentrated communities across the United States form a growing bloc of senior power that will influence the redistribution of particulariz.